The holiday of life and hope (traditions and rituals of Nowruz among Karakalpaks) - Zemfira I. Kurbanova (Историческая этнология, 2025)
The article examines the celebration of Nowruz (Nowryz among the Karakalpaks), one of the most significant and revered holidays in the culture of many peoples of the Muslim world, including Central Asia and the Karakalpaks. Despite the fact that Nowruz is not a religious holiday, it has been officially recognized in Muslim Iran and is widely celebrated in the agricultural oases of Central Asia. Unlike religious holidays, the date of which is determined by the movable lunar calendar, Nowruz is celebrated annually in spring of the solar calendar on the day of the vernal equinox. This holiday symbolizes the beginning of a new year, celebrating the awakening of nature and a new life cycle. Nowruz has a deep symbolism and occupies an important place in the traditional worldview of the Central Asia peoples. Its celebration is associated with the veneration of natural forces, the unity of man with the world around him, and rituals aimed at ensuring well-being, health, and prosperity in the coming year. It is a time of joy, hope and new beginnings, when people come together to share a meal, exchange gifts and express good wishes. During the Soviet era, traditional holidays underwent significant changes: the scale of religious and folk celebrations was diminished, and they transformed from official public events with mass celebrations into family celebrations. The same fate befell Nowruz. The extensive festivities of Nowruz were first reduced to local celebrations, and then disappeared altogether. The revival of the holiday is associated with the post-Soviet period, and today Nowruz is an integral part of the cultural heritage of the peoples of Central Asia. It retains its connection with centuries-old traditions and is passed down from generation to generation.